Understanding the Multiple Influences on Black Parents’ School Involvement: A Longitudinal Perspective - Adrian Gale; Ed-Dee Williams; Donte Boyd; Husain Lateef (Children, 2024)
This study explores longitudinal influences of various factors on Black parents’ involvement in their children’s education. Guided by Hoover-Dempsey & Sandler’s Model of Parent Involvement, this research examines whether parents’ school climate perceptions, attitudes about involvement, self-efficacy, and children’s academic performance predict parent involvement over time. Utilizing data from the Maryland Adolescence in Context Study with a sample of 560 Black parents, we found that positive school climate perceptions and favorable attitudes towards involvement significantly predict increased parent involvement in later years. The results underscore the importance of supportive school environments and parent attitudes in fostering their involvement.